Fasakh Nikah Due to Disease in the Islamic Family Law of Perak Malaysia: Fasakh Nikah Karena Penyakit Dalam Hukum Keluarga Islam Perak Malaysia - Abdul Muthalib, Salman (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
Scholars of Islamic jurisprudence have formulated several types of diseases that can be used to get a marriage thrown out. This topic has also been included in the Perak Islamic Family Law to regulate family life for its people. With the advancement of medical science, some of the diseases highlighted by scholars in the past have been found to be curable, while new types of diseases have emerged that pose a threat to the affected person and may affect the provisions of the Perak Family Law. Therefore, the Islamic law applied should be in line with the current developments of the time. This study examines several types of diseases in the Perak Family Law that can allow someone to file for divorce and whether these diseases are still relevant given current medical advancements. The results show that the diseases mentioned in Perak family law can no longer be used as a valid reason for the annulment of a marriage because they can be cured. This is in line with the principles of Islamic jurisprudence, which say that if the grounds for annulment have been eliminated, then the ruling should also be eliminated.